Individualized Dosimetry to Guide LuTATE Therapy in Pediatric Neuroblastoma - London, Kevin; Trpezanovski, Justine; Trahair, Toby; McCowage, Geoff (World Journal of Nuclear Medicine, 2025)
Neuroblastoma is the most common extracranial solid tumor in children. Tumor heterogeneity is a hallmark of neuroblastoma and prognosis can be dismal in the presence of high-risk factors such as N-myc gene amplification, aneuploidy, genetic rearrangement, and age at presentation. I-131 MIBG therapy has traditionally been the radionuclide therapy agent used in pediatric neuroblastoma and is incorporated in many treatment protocols. The high cost and limited availability of I-131 MIBG and the required radiation safety measures are barriers to its widespread use. LuTATE has emerged as a more practical radionuclide therapy agent requiring less stringent radiation safety measures and coupled with GaTATE PET/CT forms a potentially useful theranostic pairing for children with neuroblastoma. LuTATE therapy in adults with neuroendocrine tumors uses an empiric dosing schedule with good results. However, a previous study using empiric dosing of LuTATE in pediatric neuroblastoma was not shown to be effective. We present our use of individualized patient dosimetry to optimize the dose of LuTATE in three children with relapsed/resistant neuroblastoma.
Keywords: dosimetry; LuTATE; neuroblastoma; pediatric; theranostics